Large endocardial rheumatoid nodules: a case report and review of the literature. Issue 3 (3rd July 2017) - Vantrease, Allen; Trabue, Christopher; Atkinson, James; McNabb, Paul
ABSTRACT: Rheumatoid nodules occur frequently in patients with rheumatoid arthritis and are the most common cutaneous manifestation of the disease. Although uncommon, rheumatoid nodules may also occur on cardiac valves, where they may be large and clinically significant. They may embolize and cause stroke. They may cause regurgitant murmurs, or they may result in valvular destruction. Echocardiographically, they may mimic an atrial myxoma or appear as a vegetation. We present a patient with seronegative rheumatoid arthritis who developed an acute embolic stroke; he had peripheral stigmata of infective endocarditis on physical examination and echocardiography revealed a mitral valve vegetation. We illustrate that these findings were due to a large, highly destructive mitral valve rheumatoid nodule. We review the literature on macroscopic endocardial nodules and emphasize their diverse clinical behavior.